2007
DOI: 10.1111/j.1365-2524.2007.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Intention of adolescents to seek professional help for emotional and behavioural difficulties

Abstract: Much is known about adolescent help seeking for severe mental health problems. Little is currently understood about the professionals that adolescents would seek help from for milder emotional and behavioural difficulties. A self-report questionnaire was completed by 968 adolescents (53% male), aged 13-14 years in school year 9, and 15-16 years in school year 11 (64% male), attending a purposive sample of four medium to large secondary schools in Devon, UK, during February 2005. Questionnaires were completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Self-referral appeared to reassure PUs that help offered was confidential. The link between confidentiality and help-seeking echoes findings from studies of help-seeking in young people (Farrand, Parker, & Lee, 2007;Rickwood et al, 2005), although as accountability for mental health is a relatively new responsibility for schools (Reid, 2005) conflicting attitudes to transparency and confidentiality in schools could challenge development in this area.…”
Section: Discussionmentioning
confidence: 97%
“…Self-referral appeared to reassure PUs that help offered was confidential. The link between confidentiality and help-seeking echoes findings from studies of help-seeking in young people (Farrand, Parker, & Lee, 2007;Rickwood et al, 2005), although as accountability for mental health is a relatively new responsibility for schools (Reid, 2005) conflicting attitudes to transparency and confidentiality in schools could challenge development in this area.…”
Section: Discussionmentioning
confidence: 97%
“…cancer or mental health problems) or alcohol problem of a parent affects the well‐being of the entire family . Previous studies have shown that reasons for visiting a school health nurse include various psychosomatic symptoms and changes related to one's development as well as related support needs . When a child or adolescent describes a single symptom, such as a headache, it is also important to enquire about other symptoms, potential underlying factors and the child's overall life situation and family circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the concerns and reasons that children and adolescents cite for seeing a school nurse include psychosomatic symptoms such as headache, pain and sleeping difficulties . Adolescent depression and issues related to body image or the need to discuss family‐related matters, such as parental alcohol use, have also been reasons for visiting a school nurse …”
Section: Introductionmentioning
confidence: 99%
“…According to Larsson and Zaluha, 20 psychosomatic symptoms are also common reasons for students visiting the school nurse, including headaches (26%), stomach pain (29%), back or neck problems (11%), nervousness or worries (15%) and sadness or depression (7%). In addition, students seek help from a nurse, for example, when having problems with sleeping at night, when arguing often with their parents and encountering changes in their body 21 . School health care has an important role.…”
Section: Introductionmentioning
confidence: 99%